Long‐Term Changes and Influencing Factors of Water Quality in Aquaculture Dominated Lakes Unveiled by Sediment Records and Time Series Remote Sensing Images. Issue 11 (11th November 2022) - Chen, Cheng; Lin, Miaoli; Chen, Qiuwen; He, Mengnan; Zhang, Jianyun; Cui, Zhen; Zhu, Liujun
Abstract: Hydraulic connectivity has great effects on water quality. Enclosure aquaculture can largely alter lake flow regime and thus deteriorate water quality. Understanding the dynamics and influencing factors of water quality in enclosure aquaculture lakes is of great significance to ecosystem restoration of degraded lakes. However, it remains challenging due to the lack of long time series data. In this study, the dynamics of water quality in aquaculture dominated lakes were captured through 210 Pb and 137 Cs dating based on sediment records. Meanwhile, the effects of landscape pattern within aquaculture lakes on water quality were revealed by long time series of remote sensing images. Results showed the 210 Pb and 137 Cs sediment dating could provide an effective way to obtain long‐term series of lake water quality data in the unmonitored area. The contents of lake sediment nutrients showed an upward trend from 1960 to 2018. The transformation of lakes from agriculture dominated to aquaculture dominated had increased sediment nutrients level. The long‐term changes of lake sediment nutrients could be well explained by the landscape pattern metrics within aquaculture lakes, with an average explain power of 87.6%. The configuration metrics at class level had the most contribution (73.6%) to the changes of lake sediment nutrients, followed by the composition metrics (48.8%) and the configuration metrics at landscape level (33.4%). This study can provide a promising method to understand water quality changes in lakes with no historical monitoring data available and is of great benefit to water quality management in aquaculture dominated lakes. Plain Language Summary: Understanding the dynamics and influencing factors of water quality in enclosure aquaculture lakes is of great significance to ecosystem restoration of degraded lakes. However, it remains challenging due to the lack of long time series data. In this study, the dynamics of water quality in aquaculture dominated lakes were captured through 210 Pb and 137 Cs dating based on sediment records. Meanwhile, the effects of landscape pattern within aquaculture lakes on water quality were revealed by long time series of remote sensing images. The key contribution of this study is to provide a novel way to investigate the long‐term changes and the associated influencing factors of water quality in enclosure aquaculture dominated lakes through sediment records and time series of remote sensing images. This study also demonstrated the configuration metrics at class level had the most contribution to the changes of lake sediment nutrients in enclosure aquaculture dominated lakes, followed by composition metrics and configuration metrics at landscape level. This provide us with valuable insights into which factors determine water quality in enclosure aquaculture dominated lakes. Key Points: Long‐term changes of water quality in enclosure aquaculture dominated lakes were captured by sediment record The transformation of the lakes from agriculture dominated to aquaculture dominated had increased sediment nutrients level Landscape pattern metrics within the aquaculture lakes can well explain the long‐term changes of lake water quality